Liberal imperialism and the origins of Israel: the position of Isaiah Berlin - Silva, Elisabete Mendes (2015)
Isaiah Berlin, a British philosopher and historian of ideas,positioaed in favour oftfae creation ofthe State of Israel in 1948. Himself a Russian Jew, yet confessedly an anglophile, Berlin accounted for the advantages for the Jews ofhaving a place which they could call home. Claiming that Jews had no geography, only history, Berlm saw fhe creation of Israel as the emancipation of Jewish slavery and as the chance for the Jews to have their own nation, with coinmon national and cultural pattems, despite the difficulties it implied. Even though the state of Israel emerged with attributes quite different from those which anyone had previously mtended, there were by the time of its formation, several positions which were anticipated by the Jewish Diaspora in the world. On the one side, there were the Westem Jews and on the other the Bastem European Jews.Based on Berlia's own defence of Israel, it is this paper's main objective to analyse these distinct positions, focusing mainly on the British liberal conception of Israel, in its attempts to establish a civilising mission in the rather barbarous and undeveloped communities of the East.